1998
DOI: 10.1016/s0735-1097(98)00409-4
|View full text |Cite
|
Sign up to set email alerts
|

Administration of an intravenous perfluorocarbon contrast agent improves echocardiographic determination of left ventricular volumes and ejection fraction: comparison with cine magnetic resonance imaging

Abstract: Administration of an intravenous contrast agent improves the ability to accurately assess LV volumes and EF in humans. Contrast enhancement is most useful in subjects with two or more adjacent endocardial segments not seen at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
119
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(125 citation statements)
references
References 23 publications
2
119
1
3
Order By: Relevance
“…19 Several earlier studies investigated the influence of contrast enhancement on LV endocardial wall visibility and volume measurements using both 2DE and 3DE, as described schematically in table 2. [11][12][13][14][15][16][17][18][19][20][21][22]25 Among these, the results of two 2D studies using the ultrasound contrast agent Levovist are in line with the present study (a significant increase in LV volumes), effects that were ascribed to ultrasound contrast filling up intertrabecular space. 17,19 A similar study with EchoGen showed a small but significant decrease in LV end-diastolic volume, and no change in LV endsystolic volume and ejection fraction measurements.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…19 Several earlier studies investigated the influence of contrast enhancement on LV endocardial wall visibility and volume measurements using both 2DE and 3DE, as described schematically in table 2. [11][12][13][14][15][16][17][18][19][20][21][22]25 Among these, the results of two 2D studies using the ultrasound contrast agent Levovist are in line with the present study (a significant increase in LV volumes), effects that were ascribed to ultrasound contrast filling up intertrabecular space. 17,19 A similar study with EchoGen showed a small but significant decrease in LV end-diastolic volume, and no change in LV endsystolic volume and ejection fraction measurements.…”
Section: Discussionsupporting
confidence: 86%
“…[11][12][13][14][15][16][17] Besides improved endocardial border definition, several studies observed larger LV volumes following ultrasound contrast administration. [11][12][13][14][15][16][17][18][19][20][21][22] This may be explained by the fact that the LV contrast fills up the intertrabecular space, thereby delineating the outermost rather than the innermost endocardial contour. Although ultrasound contrast agents have the potential to improve LV volume measurement reproducibility, the question arises where the LV cavity boundaries should be drawn: i.e.…”
mentioning
confidence: 99%
“…In these cases, the use of intravenous contrast agents can improve endocardial border definition and reader confidence in the assessment of wall motion. Contrast echocardiography has been proven to improve the estimates of LVEF substantially (12,13). For example, Hundley et al (13) calculated the LVEF in 40 patients using both noncontrast and contrast echocardiography, and compared the results with those obtained using same-day magnetic resonance imaging.…”
mentioning
confidence: 99%
“…Ultrasound contrast agents that traverse the pulmonary circulation and opacify the left cardiac chambers may overcome this limitation and have proven to be important for the assessment of left ventricular (LV) border detection and function. 1,2 An overview of the use of ultrasound contrast agents was published in this journal in 1998. 3,4 SonoVue, a commercially available contrast agent, has been used in the Netherlands since 2001.…”
mentioning
confidence: 99%